english: english - Azzam Musoffa; Fuji Lestari; Safira Akmalun Ni'mah (Aqidah-ta: Jurnal Ilmu Aqidah, 2022)
The nakedness in Islam considered as one of important foundation in Islamic Jurisprudence because the debate in this area will bear to the different of limit in Hijab or veiling. Thus, this research aimed to understand the various opinions of scholars ranged from Four Great Schools until recent scholars about the nakedness of free woman and female slave in Islam to know the reason why they reached the conclusion mentioned in their writings. The method used in this research is a library research by taking the books written by Four Great School, Ibn Taymiyah, Nasiruddin al-Albani and Qassim Amin as main sources and reaching the conclusion by comparing their ideas. This research resulted some findings after observing the scholars’ ideas, on of that they divided into three opinions regarding the limit of nakedness of free woman and about the female slave it is also divided into three opinions.